2018
DOI: 10.1111/1365-2435.13114
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure in a rapidly urbanizing planet

Abstract: The human population is rapidly urbanizing, and the negative impacts of urban cover on biodiversity and ecosystem function are expected to increase. Trophic dynamics have been hypothesized to change with urbanization, with consequences for biodiversity and function. Here, I review recent progress in this area by focusing on how urbanization affects dietary sources, trophic interactions and the functional ecology of synanthropic species. Urbanization affects primary autochthonous production in terrestrial and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 120 publications
(284 reference statements)
3
46
0
1
Order By: Relevance
“…Urbanization significantly decreased leaf chewer damage, and this finding was remarkably consistent across sites throughout most of the geographic distribution of Q. robur . The observed reduction in leaf chewer damage in urban sites relative to rural sites contradicts initial work on this subject proposing that herbivory should be higher in urban habitats, presumably because urban conditions limit investment in anti‐herbivore defences or weaken predator top–down control of herbivore populations (reviewed by Dreistadt et al 1990, Raupp et al ). Interestingly, our results are not alone as a few recent studies have similarly reported decreases in insect herbivory, particularly by leaf chewers, with urbanization (Herrmann et al 2012, Bode and Gilbert 2016, Kozlov et al 2017).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Urbanization significantly decreased leaf chewer damage, and this finding was remarkably consistent across sites throughout most of the geographic distribution of Q. robur . The observed reduction in leaf chewer damage in urban sites relative to rural sites contradicts initial work on this subject proposing that herbivory should be higher in urban habitats, presumably because urban conditions limit investment in anti‐herbivore defences or weaken predator top–down control of herbivore populations (reviewed by Dreistadt et al 1990, Raupp et al ). Interestingly, our results are not alone as a few recent studies have similarly reported decreases in insect herbivory, particularly by leaf chewers, with urbanization (Herrmann et al 2012, Bode and Gilbert 2016, Kozlov et al 2017).…”
Section: Discussionmentioning
confidence: 74%
“…Leaf burst in this deciduous species usually occurs during April in southern Europe and in May for northern Europe, whereas leaf senescence and leaf drop typically start in September for northern Europe and in October for southern Europe. In its native range, Q. robur supports a diverse community of specialist (and a few generalist) insect herbivores such as leaf chewers, miners and gallers (Southwood et al 2005, Tack et al , Tack and Roslin 2011, Castagneyrol et al 2012, Giffard et al 2012, Moreira et al 2017, 2018a).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations